Light and energy based therapeutics for genitourinary syndrome of menopause: Consensus and controversies. Issue 2 (21st February 2017) - Tadir, Yona; Gaspar, Adrian; Lev‐Sagie, Ahinoam; Alexiades, Macrene; Alinsod, Red; Bader, Alex; Calligaro, Alberto; Elias, Jorge A.; Gambaciani, Marco; Gaviria, Jorge E.; Iglesia, Cheryl B.; Selih‐Martinec, Ksenija; et al.
Abstract : Gynecologist and plastic surgeons pioneered the application of lasers in medicine and surgery almost 5 decades ago, initially used to treat cervical and vaginal pathologies. Ever since, energy‐based devices have been deployed to treat pelvic pathologies and improve fertility. Recent technological developments triggered an unprecedented wave of publications, assessing the efficacy of fractional laser, and radiofrequency on the vaginal wall in reversing natural aging processes. Studies have shown that a certain degree of thermal energy deposited on the vaginal wall stimulates proliferation of the glycogen‐enriched epithelium, neovascularization, and collagen formation in the lamina propria, and improves natural lubrication and control of urination. This review aimed to review such data and to guide future research. A unique assembly of experts from around the globe, compiled and edited this manuscript based on a thorough literature review and personal experience. Lasers Surg. Med. 49:137–159, 2017. © 2017 Wiley Periodicals, Inc.